Preparation of SrVO3 by annealing of Sr2V2O7 in a reducing atmosphere - Edward Lee; Richard A. Harris; Jacobus J. Terblans; Elizabeth Coetsee; Vinay Kumar; Hendrik C. Swart (Chemical Physics Impact)
This study focuses on the synthesis of SrVO3 through the reduction of Sr2V2O7 by annealing in a reducing atmosphere. The effects of annealing temperature and annealing duration on Sr2V2O7 were investigated. The X-ray powder diffraction pattern showed that stoichiometric changes to Sr2V2O7 were achieved only at an elevated annealing temperature of 1000 °C in a reducing atmosphere, and that the desired SrVO3 was obtained only after 144 h of annealing. Further investigation of SrVO3 was performed using X-ray photoelectron spectroscopy, which confirmed that the reduction of V5+ found in Sr2V2O7 to V4+ found in SrVO3 was achieved.